Genesis of the Lengshuikeng Pb-Zn Deposit, China: Constraint from In-situ LA-ICP-MS Analyses of Minor and Trace Elements in Sphalerite. Issue 1 (1st December 2019) - Gong, Xuejing; Lü, Qingtian; Meng, Guixiang; Yan, Jiayong; Zhao, Jinhua
Summary: It is generally believed that at medium and low temperature, Pb and Zn are still difficult to precipitate and form porphyry mineralization due to the high solubilities. However, the Lengshuikeng deposit in Jiangxi Province is considered to be a porphyry lead-zinc deposit according to the close temporal and spatial relationship between Pb-Zn mineralization and the granite porphyries. To check the metal source of the Lengshuikeng deposit, we investigated the sphalerite using in situ analysis techniques (LA-ICP-MS, EMPA), to constrain the metal source and the mineralization temperature. The analysis results suggest that the Lengshuikeng deposit is a kind of hydrothermal deposits which formed in middle-low temperature environment and the ore-forming material dominantly comes from the porphyry magma system.